The effects of fins number and bypassed energy fraction on the solidification process of a phase change material. (October 2021) - Mohammad Olfat, Babak; Talati, Faramarz
Highlights: The solidification of the PCM inside the cylindrical containers was modeled, validated, and investigated. The effects of different boundary conditions and fins number on the freezing process of the PCM were studied. Bypassed energy from the fins to the PCM that reduces the fins performance was analyzed. Bypassed energy fraction criterion was proposed and used to evaluate the fins performance. Abstract: Nowadays, utilizing latent heat thermal energy storage systems containing phase change materials (PCMs) has been considered one of the best ways for integrating and optimizing thermal energy systems. Although using fins has been suggested by many researchers for the heat transfer enhancement in these systems, this technique is not sufficient in some cases. So, finding its reasons is the main purpose of this paper. For this aim, four different cylindrical containers, one without fins and the others with radial fins, were intended. Then, solidification of the PCM inside the containers under the constant and time-dependent first, second, and third type boundary conditions was modeled by the finite volume method based on the enthalpy formulation. To analyze fins performance, bypassed energy fraction ( β ) criterion was proposed. The results show that under the first type boundary condition, the value of β is zero, and the fins have a major effect on the heat transfer enhancement, but under the second and third type boundary conditions, the value of this parameter is significant, and the fins have a lower effect. Furthermore, it is found that by increasing the fins number, the value of β and complete freezing time decreased. The results of this study were compared and validated with the results of the analytical approach.